Laparoscopic Surgery for Colon Cancer with Intestinal Malrotation: A Case Report and Review of the Literature in Japan - Yamamoto, Manabu; Sakata, Kazuhito; Yano, Hiroko; Gion, Tomonobu; Tominaga, Yohei; Kobayashi, Hiroyuki; Tuneyoshi, Masazumi (Archives of Clinical and Medical Case Reports, 2021)
Colorectal cancer with intestinal malrotation is very rare, while intestinal malrotation is one of congenital anomaly that is rare in adults. We thus report a case of sigmoid colon cancer with intestinal malrotation treated by laparoscopic surgery. A 39-year-old woman was admitted to our hospital with constipation. A colonoscopy revealed the sigmoid colon tumor. Three-dimensional abdominal enhanced computed tomography showed that small and large intestines occupied the right- and left-side of the abdominal cavity, respectively. Her diagnosis was the sigmoid colon cancer with nonrotation type of intestinal malrotation, and she underwent laparoscopic sigmoidectomy. There have been 43 cases reports of colorectal cancer with intestinal malrotation who underwent laparoscopic surgery in Japan medical literatures. Colorectal cancer was in the right-side in 69.8% of these cases, although that in the left-side is generally more common. Three-dimensional abdominal enhanced computed tomography angiography can reveal vascular anatomic anomalies to allow laparoscopic surgery to be performed safety.